MODEL PREFERENSI KONSUMEN TERHADAP PERBANKAN SYARIAH - Purnamie Titisari; Arnis Budi Susanto (Sekolah Tinggi Ilmu Ekonomi Semarang, 2020)
This study aims to build a model of consumer preference in choosing Islamic banking. This study uses a comparative study between people's understanding of Islamic banking and conventional banking which is influenced by several factors. The sample in this study amounted to 200 people who had different backgrounds. Existing data were analyzed using Structural equation models (SEM). The research results show that there is a level of understanding and preference of the community towards different Islamic banking which is influenced by several factors developed in this research model. In the next research, it is expected to conduct an assessment of the decision to choose Islamic and conventional banking products that concentrate more on specific products in Islamic banking. In addition, further research is expected to take into account environmental factors and government policies as well as other factors that have not been studied in this study so that it is expected to enrich the knowledge in the field of management, especially consumer preferences and decision making using Islamic banking products